1968
DOI: 10.1139/o68-153
|View full text |Cite
|
Sign up to set email alerts
|

Action of proteolytic enzymes on wheat gluten

Abstract: Papain and trypsin partially hydrolyzed wheat gluten dispersed in 10% sodium salicylate, and pepsin partially hydrolyzed gluten dispersed in aluminium lactate. Trypsin was considerably less effective than either papain or pepsin. Papain produced non-protein nitrogen most rapidly during early stages of hydrolysis but pepsin produced the largest total after 48 h. The rate of release of terminal amino nitrogen was similar for papain and pepsin, and release was not complete after 48 h. The mean size of polypeptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
5
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
4
5
0
Order By: Relevance
“…The increase in gluten solubility by Corolase hydrolysis is in agreement with results obtained with different proteases (Yang and McCalla 1968, Batey 1985, Thébaudin 1990, Mimouni et al 1994, Chobert et al 1996. The comparison of the hydrolysates and their soluble fractions showed that, independent of the hydrolysis level, all peptides were very soluble at pH 4 with 0.2% NaCl.…”
Section: Solubility Of Gluten Hydrolysates As a Function Of Ph Level supporting
confidence: 87%
See 2 more Smart Citations
“…The increase in gluten solubility by Corolase hydrolysis is in agreement with results obtained with different proteases (Yang and McCalla 1968, Batey 1985, Thébaudin 1990, Mimouni et al 1994, Chobert et al 1996. The comparison of the hydrolysates and their soluble fractions showed that, independent of the hydrolysis level, all peptides were very soluble at pH 4 with 0.2% NaCl.…”
Section: Solubility Of Gluten Hydrolysates As a Function Of Ph Level supporting
confidence: 87%
“…77(4): [414][415][416][417][418][419][420] Gluten solubility was improved by enzymatic proteolysis at moderate acidic pH level. Much research focused on chemical or enzymatic modifications has resulted in the enhancement of its solubility, foaming, and emulsifying properties (Yang and McCalla 1968, Batey 1985, Bollecker et al 1990, Thébaudin 1990, Kato et al 1991, Mannheim and Cheryan 1992, Mimouni et al 1994, Babiker et al 1996. Emulsifying and foaming properties of hydrolysate dispersions at 3.75 mg/mL decreased with the increasing DH at all pH levels and salt conditions investigated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3. These results are consistent with those of a report by Yang and McCalla 16. Papain at a concentration of 0.33% decreased peak, trough, final viscosity, and the integral area of the viscosity curve by 34, 36, 32, and 37% over control solutions (CTRL), respectively.…”
Section: Resultsmentioning
confidence: 98%
“…Papain, pepsin, trypsin, and dithiothreitol (DTT) are often effective in wheat protein hydrolysis 15, 16. Wheat proteolysis results in mixtures of peptides of different molecular sizes, depending on the degree of hydrolysis (DH) and hydrolytic reagent.…”
Section: Introductionmentioning
confidence: 99%